External focus instruction using a paper balloon: impact on trunk and lower extremity muscle activity in isometric single-leg stance for healthy males - Koji Murofushi; Koji Murofushi; Tsuyoshi Morito; Hiroshi Akuzawa; Tomoki Oshikawa; Yu Okubo; Koji Kaneoka; Sho Mitomo; Sho Mitomo; Kazuyoshi Yagishita (Frontiers Media S.A., 2024)
IntroductionCore stability is crucial for preventing and rehabilitating lumbar spine injuries. An external focus instruction using a paper balloon is an effective way to activate the trunk muscles. However, the degree of trunk and lower extremity muscle activation during single leg stance with external focus instruction using a paper balloon is unknown. This study aimed to investigate the core muscle involving activity in the trunk and lower extremities on both the support and non-support sides with or without using external focus instruction using a paper balloon during isometric single-leg stance.MethodsThirteen healthy males aged 20-28 years volunteered to take part in this study and performed a single leg stance task with and without an external focus instruction, pressing their non-supporting foot onto a paper balloon without crushing it. The participant's muscle electrical activity was recorded during the single leg task using surface EMG and intramuscular EMG for six trunk muscles (transversus abdominis, internal oblique, external oblique, rectus abdominis, multifidus, and lumbar erector spinae) and five lower extremity muscles (gluteus maximus, gluteus medius, adductor longus, rectus femoris, and biceps femoris)ResultsCompared to the normal single leg stance, the external focus instruction task using a paper balloon showed significantly increased transversus abdominis (p < 0.001, p < 0.001), internal oblique (p = 0.001, p < 0.001), external oblique (p = 0.002, p = 0.001), rectus abdominal (p < 0.001, p < 0.001), lumbar multifidus (p = 0.001, p < 0.001), lumbar erector spinae (p < 0.001, p = 0.001), adductor longus (p < 0.001, p < 0.001), rectus femoris (p < 0.001, p < 0.001), and biceps femoris (p < 0.010, p < 0.001) muscle activity on the support and non-support sides.ConclusionIn conclusion, external focus instruction using a paper balloon significantly activates the trunk and lower extremities muscles on both the support and non-support sides. This finding provides insights for designing programs to improve coordination and balance. The benefits extend to diverse individuals, encompassing athletes, tactical professionals, and the general population, mitigating the risk of injury or falls linked to inadequate lower limb balance.